Surface-Enhanced Raman Scattering
DOI: 10.1007/3-540-33567-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Immunoassays Based on Surface-Enhanced Raman Scattering by Immunogold Labels

Abstract: Surface enhanced Raman scattering (SERS) spectroscopy has been reported as an ultrasensitive detecting method. Adding salts is a main way to induce nanoparticles aggregation to obtain giant enhancement of Raman signal. However, this method needs more procedures and the adding salts may interfere the detection reaction. Here an effective and simple method is reported to enhance SERS effect of the aggregation of silver nanoparticles (Ag NPs) induced by the laser of 633 nm. Ag NPs were prepared by plasmon-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Our laboratory has focused on the development of highly sensitive immunoassays ( Fig. 2 A) for several diseases ( e.g., tuberculosis and prostate and pancreatic cancer) read out by surface-enhanced Raman scattering (SERS) [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. This platform uses extrinsic Raman labels (ERLs), which are composed of gold nanoparticles coated with a Raman reporter molecule (RRM), tracer antibodies (Abs), and a capture substrate, which consists of a layer of antibodies adsorbed on a smooth gold film supported by a glass substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has focused on the development of highly sensitive immunoassays ( Fig. 2 A) for several diseases ( e.g., tuberculosis and prostate and pancreatic cancer) read out by surface-enhanced Raman scattering (SERS) [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. This platform uses extrinsic Raman labels (ERLs), which are composed of gold nanoparticles coated with a Raman reporter molecule (RRM), tracer antibodies (Abs), and a capture substrate, which consists of a layer of antibodies adsorbed on a smooth gold film supported by a glass substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of reports have examined the impact of excitation wavelength on the SERS enhancement factor (EF) and, therefore, measurement sensitivity. 54,55 With respect to the assay in Scheme 1, we previously showed how the EF depends on the plasmonic coupling between the AuNPs that constitute the core of the ERLs and the planar gold capture surface. 54 This work demonstrated that: (1) coupling shifts the LSPR of the system and, as a consequence, the optimal excitation wavelength for assay readout; and (2) the EF is largest when the maximum in LSPR (λ max ) falls midway between the excitation wavelength (λ excit ) and that of the scattered radiation (λ scat ).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of the aforementioned plasmonic coupling, the λ max of 540 nm for 60 nm AuNPs suspended in 2 mM borate buffer is redshifted by nearly 80 nm to 618 nm. 54,55 Furthermore, the coupling causes a shift in λ max from the optimal midpoint between λ excit and λ scat by 44 and 213 nm for the benchtop and handheld spectrometers, respectively. Offsets of ∼50 nm can lower the EF by an order of magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent breakthroughs have greatly simplified hardware, yielding high performance, compact, rugged, and portable instruments at affordable prices, $10K-$15K. 30 In other words, advances in optical filters, array detectors, and fiber optics have moved Raman spectroscopy from the research laboratory to the industrial plant floor and other demanding environments, while maintaining a high level of performance.…”
Section: Introductionmentioning
confidence: 99%